Acute stress disorder in a ten year old child following a major earthquake - Gautam, Kamal; Upadhyaya, Shreeram; Pant, Sagun Ballav; Dhungana, Saraswati; Tulachan, Pratikchya; Chapagai, Manisha; Ojha, Saroj Prasad (Journal of Kathmandu Medical College, 2017)
Acute stress disorder is a syndrome characterized by the development of severe anxiety, dissociative and other symptoms that occur between three days to one month after exposure to an extremely traumatic or stressful life event. This case report presents a 10-year old girl child that presented with an acute stress disorder after being rescued from a state of burial for three and half hours inside a demolished house following a major earthquake. She was admitted to Psychiatry ward for eight days and was discharged successfully in a pre-morbid state after psychological interventions. With this particular child’s presentation in the emergency following a major traumatic event, we can learn to address and timely manage the secondary psychological trauma the child, her family and other relatives may undergo. Journal of Kathmandu Medical College Vol. 5, No. 3, Issue 17, Jul.-Sep., 2016, page: 98-100